Fused High-Speed UAV Target Tracking Algorithm - Zhang, Yu; Cui, Mengqi; Ji, Baokun; Wang, Haojian (International Journal of Mechanical and Electrical Engineering, 2025)
To achieve precise tracking and aiming in ground-based laser strikes against drones, this paper proposes a high-speed target tracking algorithm adapted for UAVs (Unmanned Aerial Vehicle) in aerospace backgrounds. The algorithm integrates the KCF algorithm with a custom simple template matching algorithm and optimizes the custom template matching method using NEON. On the Nvidia Orin NX, this approach significantly improves tracking real-time performance compared to using KCF alone. Applying this tracking strategy to a custom dataset and parts of the ANTI-UAV dataset yielded good tracking results.